Uma conversa com e sobre Salete Maria da Silva - da Silva, Andréa Betânia; de Lucena, Bruna Paiva; de Lucena, Bruna Paiva (Boitatá, 2020)
Salete Maria da Silva is, before any characterization, a woman with the soul and feet of the hinterland, who learned to make string with one of her grandmothers, and, not by chance, the lives of us women run through all her work, be it cordelística - with a strong feminist and revolutionary content -, either the academic, as a professor of the Bachelor of Gender and Diversity Studies at the Federal University of Bahia (UFBA). In her nearly 30 years dedicated to creating feminist and libertarian strings, she has published more than a hundred tracts, many of which can be read on her blog Cordelirando. She is a founding member of the Sociedade dos Cordelistas Mauditos, an important collective of poets, singers and performers founded in 2000, in Juazeiro do Norte / CE. This interview is a great conversation in which four people participate: Salete Maria, Andréa Betânia, Bruna Lucena and José Gomes, the first being the one interviewed; the next two, the interviewers; and the last, responsible for the literal transcription. We adopted conversation as a method of conducting this interview because we believe that it is "[...] a non-hierarchical summoning of different knowledge", in which "[...] knowledge is always in the plural, knowledge(s)", how Maria Luiza Süssekind and Raphael Pellegrini defend We talked on October 6, 2020, in a video call filled with stories of lives, the arts of yesterdays and ancestral now, about their disturbing presence in the cordelístico scene. Faced with the impossibility of establishing a linear conversation with Salete - which we understand as a positive point - in view of the exposition of a thought that reminds us of a palimpsest, the topics covered emerged motivated not only by our curiosity as an interviewer, but above all , by the mottos with which the interviewee presented us as she tried to retrace her personal and poetic trajectory, following a route that allowed herself to be guided by her restless and disturbing way of being in the world. When we choose to use, in the title of this interview, "with" and "about", without deciding on just one, it is less about a willingness to choose and decide, and more, much more, about a willingness to realize what is the intimacy of sharing words, attentive listening, knowledge, as well as showing this important cordelist of our here and now.